Concrete Corrosion Cracking and Transverse Bar Strain Behavior in a Reinforced Concrete Column under Simulated Marine Conditions - Gyeongcheol Choe; Yasuji Shinohara; Gyuyong Kim; Sangkyu Lee; Euibae Lee; Jeongsoo Nam (Applied Sciences, 2020)
This study performed accelerated corrosion tests on reinforced concrete (RC) specimens reinforced with transverse steel bars to evaluate the concrete cracking and rebar strain behaviors caused by rebar corrosion. Seven RC specimens were created with variable compressive strengths, rebar diameters, and concrete cover thicknesses. To mimic in-situ conditions, the accelerated corrosion tests applied a current to the longitudinal bar and transverse bar for different periods of time to create an unbalanced chloride ion distribution. These tests evaluated the amount of rebar corrosion, corrosion cracking properties, and transverse bar strain behavior. The corrosion rate of the transverse bar was faster than that of the longitudinal bar, and cracking first occurred in the concreate around the transverse bar in the specimens with low concrete compressive strength and thin concrete cover. Corrosion cracking and rebar strain were greatly affected by the behavior of the corrosion products that resulted from the pore volume and cracking properties of the cement paste.